Taming Eschatology: The Case of Silja Walter OSB - Bernard Łukasz Sawicki; Chiara Tacchinardi (Polonia Sacra)
This paper examines the eschatological themes in the series of poems, The Dance of Obedience or the Straw Carpet, written by the Benedictine nun Silja Walter (1919–2011) — Sr. Hedwig OSB from the Swiss monastery of Fahr. This series of poems is particu- larly representative for the poet’s work as it combines her monastic experience with her personal poetic reading of the Bible in the spirit of lectio divina. These two sourc- es give the analyzed poetry a particular theological quality, originally combining spiritual and dogmatic elements. Having presented the biographical and monastic context of the set in question, the authors show the form, connections and dynamism of the eschatological themes present in the discussed poetry. In conclusion, referring generally to the entirety of Walter’s work, they show the anthropological value of her approach to eschatology, which, in accordance with the title of the article, can be defined as bringing eschatological themes closer to everyday existential experience. This effect is possible thanks to the original use of poetic language.